1998
DOI: 10.1161/01.str.29.8.1721
|View full text |Cite
|
Sign up to set email alerts
|

Dural-Pial Arteriovenous Malformation After Sinus Thrombosis

Abstract: Background-We report an unusual case of acquired dural-pial arteriovenous malformation (AVM) following sinus thrombosis. Case Description-Initial angiography performed in a 39-year-old man showed thrombosis of the superior sagittal sinus (SSS) and the right transverse sinus (TS) but no vascular malformations. Follow-up angiography 29 months later revealed recanalization of the SSS and the TS, retrograde cortical venous drainage which suggested that thrombosis of the sinuses probably propagated into the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 12 publications
(11 reference statements)
1
27
0
1
Order By: Relevance
“…This case supports the theory that some cranial fistulae are acquired1 and can rarely be mixed pial-dural 2. Dural AVFs cause venous hypertension and ischaemia, which may directly elevate vascular endothelial growth factor (VEGF),3 or indirectly through decreased cerebral perfusion pressure 4 5.…”
Section: Case Reportsupporting
confidence: 81%
“…This case supports the theory that some cranial fistulae are acquired1 and can rarely be mixed pial-dural 2. Dural AVFs cause venous hypertension and ischaemia, which may directly elevate vascular endothelial growth factor (VEGF),3 or indirectly through decreased cerebral perfusion pressure 4 5.…”
Section: Case Reportsupporting
confidence: 81%
“…Typically, dural AVMs are acquired lesions, occurring as a result of trauma, surgical procedures, or sinus thrombosis. 6,7,9,11 In contrast, cerebral AVMs (pial AVMs) are considered to be congenital lesions. During the second to fifth stage of Streeter craniocerebral vascularization, the primitive vascular plexus within the embryonic brain differentiates into arterial, capillary, and venous components.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Venous hypertension may foster the growth of microscopic arteriovenous shunts found within the vasa vasorum of the normal pachymeninges and/or may stimulate the release of angiogenic factors. [22][23][24][25] Ozawa et al 26 recently reported a case of a pial arteriovenous malformation with dural supply occurring after an episode of dural sinus thrombosis. In their case, dural sinus thrombosis resulted in a remote, pial arteriovenous malformation with meningeal arterial supply.…”
Section: Discussionmentioning
confidence: 99%